Robot-assisted arthroscopic all-epiphyseal PCLR with remnant preservation in a 13-year-old boy: a case report and review of the literature - Liao, Chaofan; Zheng, Jiang; Liang, Qiuzhen; Liu, Peidong; Pang, Panpan; Zhang, Liang (Frontiers in Surgery, 2025)
PurposeThere is limited research worldwide on posterior cruciate ligament (PCL) tears in pediatric and adolescent patients (PAPs). This report aims to present our treatment method as a potential reference for clinical surgery.MethodsWe report the case of a 13-year-old boy with a PCL tear who underwent robot-assisted arthroscopic all-epiphyseal PCL reconstruction (PCLR) with remnant preservation using the TiRobot surgical robot. The patient was followed for 6 months postoperatively.ResultsThe surgery lasted 110 min, involving four x-ray exposures and a single guide pin insertion, without requiring positional adjustment. Postoperative magnetic resonance imaging on day 2 confirmed that the femoral and tibial bone tunnels were within the epiphysis, with good graft fixation. The angle between the reconstructed tibial bone tunnel and the graft was approximately 104.1°. Sutures were removed after 2 weeks, showing good wound healing and full extension of the affected limb. By 8 weeks, the patient had regained full knee flexion, and by 12 weeks, muscle strength of the affected limb exceeded 85% of that in the contralateral side, allowing the patient to start jogging. By 16 weeks, the patient resumed badminton training. At the last follow-up, knee function had markedly improved, with the preoperative International Knee Documentation Committee score increasing from 43.68 to 82.76 and the Lysholm score increasing from 46 to 95.ConclusionArthroscopic all-epiphyseal PCLR with remnant preservation, assisted by the TiRobot orthopedic robot navigation system, demonstrated several clinical advantages. The technique theoretically avoids damage to the PAPs’ growth plate, preserves the PCL remnants, reduces the “killer turn” effect, and minimizes the risk of injury to surrounding blood vessels and nerves. Serial radiographic evaluations during the 6-month follow-up revealed no evidence of physeal damage in this case.